Is all publicity good publicity? The impact of direct and indirect media pressure on the adoption of governance practices - Shipilov, Andrew V.; Greve, Henrich R.; Rowley, Timothy J. (Strategic Management Journal, 2019)
Abstract Research Summary Media coverage is known to influence firms' behavior, but it is less known whether coverage of firms' partners also has an effect. In a context of governance practices' diffusion in Canada, we distinguish the effect of direct media coverage of the firm's activities, from indirect coverage, defined as media coverage of the firms' interlock partners. We examine whether the coverage is laden with positive or negative emotions. We find that both direct and indirect media coverage have a strong effect on firms' adoption of practices, either when the tone is positive or negative. The findings indicate that media coverage has broader and deeper effects on firms' actions than previously known. Managerial Summary Firms are under pressure from many outside stakeholders who want them to change. This pressure is felt strongly when it is expressed through mass media attention to the firms or their practices, and often persuades management to make changes. We examine the effect of media coverage on changes in governance practices, finding that media influences reach all the way to the board. In addition, we find that both critique and praise can lead a firm to make changes in its governance practices. The media attention does not even have to be directed to the firm itself: when media targets companies that share common directors with the focal firm, the firm's board usually responds by adopting governance practices as if media targeted the firm.